Impact of rehabilitation dose on body mass index change in older acute patients with stroke: a retrospective observational study - Murata, Hiroyasu; Tashiro, Syoichi; Sakamoto, Hayato; Ishida, Rika; Kuwabara, Mayuko; Matsuda, Kyohei; Shiokawa, Yoshiaki; Hirano, Teruyuki; Momozaki, Ryo; Maeda, Keisuke; Wakabayashi, Hidetaka; Yamada, Shin (Frontiers in Nutrition, 2023)
Background It is established that a low body mass index (BMI) correlates with a diminished home discharge rate and a decline in activities of daily living (ADL) capacity among elderly stroke patients. Nevertheless, there exists a paucity of knowledge regarding strategies to mitigate BMI reduction during the acute phase. This investigation seeks to elucidate the impact of rehabilitation dose, as determined by both physical and occupational therapy, on BMI alterations, positing that a heightened rehabilitation dose could thwart BMI decline. Methods This retrospective, observational study was conducted in the stroke unit of a university hospital. Enrollees comprised individuals aged ≥65 years, hospitalized for stroke, and subsequently relocated to rehabilitation facilities between January 2019 and November 2020. The percentage change in BMI (%ΔBMI) was calculated based on BMI values at admission and discharge. Multivariate multiple regression analysis was employed to ascertain the influence of rehabilitation dose on %ΔBMI. Results A total of 187 patients were included in the analysis, of whom 94% experienced a reduction in BMI during acute hospitalization. Following adjustment for sociodemographic and clinical factors, multivariable analyzes revealed a positive association between rehabilitation dose and %ΔBMI (β = 0.338, p < 0.001). Conclusion The findings of this study suggest that, in the context of acute stroke treatment, an augmented rehabilitation dose is associated with a diminished decrease in BMI.